2018
DOI: 10.1002/adma.201800140
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped CoP Electrocatalysts for Coupled Hydrogen Evolution and Sulfur Generation with Low Energy Consumption

Abstract: Hydrogen production is the key step for the future hydrogen economy. As a promising H production route, electrolysis of water suffers from high overpotentials and high energy consumption. This study proposes an N-doped CoP as the novel and effective electrocatalyst for hydrogen evolution reaction (HER) and constructs a coupled system for simultaneous hydrogen and sulfur production. Nitrogen doping lowers the d-band of CoP and weakens the H adsorption on the surface of CoP because of the strong electronegativit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
219
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(234 citation statements)
references
References 72 publications
10
219
0
5
Order By: Relevance
“…[13] Theoretical and experimental investigations have illuminated that, in addition to capturing electrons from metal atoms,Patoms embed in the lattice of TMPs can work as carriers to trap protons during HER process owing to its high electronegativity.I ti sn oteworthy that, however, there is ad ifference between the hydrogen adsorption Gibbs free-energy (DG H* )onthe surface of TMPs and the thermoneutral DG H* value of 0eVf or the optimal HER activity. [14] Forexample,the DG H* value of CoP is much negative, [15] indicating that the desorption of adsorbed hydrogen (H*) to form H 2 is the rate-determining step of the whole HER. [16] Furthermore,t he high concentration of Pi n TMPs also weakens the delocalization capacity of electrons in metal atoms,r esulting in lowering the conductivity of TMPs severely.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Theoretical and experimental investigations have illuminated that, in addition to capturing electrons from metal atoms,Patoms embed in the lattice of TMPs can work as carriers to trap protons during HER process owing to its high electronegativity.I ti sn oteworthy that, however, there is ad ifference between the hydrogen adsorption Gibbs free-energy (DG H* )onthe surface of TMPs and the thermoneutral DG H* value of 0eVf or the optimal HER activity. [14] Forexample,the DG H* value of CoP is much negative, [15] indicating that the desorption of adsorbed hydrogen (H*) to form H 2 is the rate-determining step of the whole HER. [16] Furthermore,t he high concentration of Pi n TMPs also weakens the delocalization capacity of electrons in metal atoms,r esulting in lowering the conductivity of TMPs severely.…”
Section: Introductionmentioning
confidence: 99%
“…DFT calculations revealed that N‐doping could not only reduced the ΔG H on the major Co sites for enhancing the intrinsic HER activity, but also optimized the ΔG H on the neighboring S sites for offering the extra catalytic active sites, finally resulting in the considerable HER performance improvement (Figure b and 7c). The N‐doping effects on CoP electrocatalysts for HER were also studied . The introduction of N dopants could remarkably improve HER activity ( η 10 =−42 mV and Tafel slope=41.2 mV/dec) (Figure d), which is far better than that of the pristine CoP ( η 10 =−85 mV and Tafel slope=50.5 mV/dec) and even comparable to that of Pt/C benchmark ( η 10 =−33 mV and Tafel slope=30.1 mV/dec).…”
Section: Transition‐metal‐based Multivariate Compounds For Hermentioning
confidence: 99%
“…Among various structures, 1D hetero‐nanowires have been demonstrated to be superior for gas‐involving electrocatalysis; this is mainly attributed to their abundant, well‐exposed active sites; efficient charge transfer; and unique surface properties for gas evolution and release . Apart from structure engineering, regulating the composition of electrocatalysts by heteroatom doping is another alternative strategy to boost the catalytic activity . Of particular interest is the nitrogen anion dopant, which has demonstrated its utility for modifying the functionalities and properties of transition‐metal‐based electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the group of Xie reported that the introduction of N − anions could improve the electrocatalytic HER activity of Ni 3 S 2 and CoS 2 . Zhang and co‐workers found that N doping could lower the d band of CoP and weaken H adsorption on the CoP catalyst surface, resulting in improved performance for simultaneous H 2 and sulfur production . Despite these advances, the combination of an interface engineering and heteroatom anion decoration strategy for constructing highly efficient HER–OER bifunctional N‐decorated heterogeneous 1D nanostructures has rarely been explored to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation